Clinical and x-ray oral evaluation in patients with congenital Zika Virus - Carvalho, Isabella Fernandes (2019)
Objective: The aim of this study was to investigate possible malformations in the soft, bone and/or dental tissues in patients with congenital Zika Virus (ZIKV) by clinical and x-ray evaluation. Methodology: Thirty children born with ZIKV and 30 children born without ZIKV (control group) were included in the study. Patients were evaluated over 24 consecutive months according to the variables: sex, age, cleft palates, soft tissue lesions, alveolar ridge hyperplasia, short labial and lingual frenums, inadequate posture of the lingual and perioral muscles at rest, micrognathia, narrow palatine vaults, changes in the teeth shape and/or number, sequence eruption, spasms, seizures and eruption delay were evaluated. Chi-square test, Student’s t-test and nominal logistic regression were used (p<0.05). Results: Among the 30 babies examined, the mean age of the first dental eruption was 10.8±3.8 with almost two-thirds of the children (n=18, 60%) experiencing eruptions of their first tooth after 9 months of age, nine children (30%) had inadequate lingual posture at rest, more than half of the children (n=18, 60%) had short labial or lingual frenums. ZIKV babies showed a high prevalence of clef palate (p<0.001), inadequate lingual posture at rest (p=0.004), micrognathia (p=0.002), changes in the shape and/or number of teeth (p=0.006), alteration in sequence of dental eruption (p<0.001) and muscles spasms (p=0.002). The delay eruption was associated with inadequate lingual posture at rest (p=0.047), micrognathia (p=0.002) and changes in the shape and/or number of teeth (p=0.021). The delayed eruption (p=0.006) and narrow palatine vaults (p=0.008) were independently associated with ZIKV. Moreover, female patients showed the most narrow palatine vaults (p=0.010). Conclusions: The children with ZIKV showed a greater tendency to have delayed eruption of the first deciduous tooth, inadequate lingual posture and short labial and lingual frenums.